2001
DOI: 10.1038/86715
|View full text |Cite
|
Sign up to set email alerts
|

A biodegradable polymer as a cytokine delivery system for inducing bone formation

Abstract: Bone morphogenetic proteins (BMPs) that have the potential to elicit new bone in vivo have been used in a tissue-engineering approach for the repair of bone injuries and bone defects. Although it is now possible to generate large amounts of recombinant human (rh) BMPs for medical use, the major challenge remains in the development of optimal local delivery systems for these proteins. Here we describe the development of a synthetic biodegradable polymer, poly-d,l-lactic acid-p-dioxanone-polyethylene glycol bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
146
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(153 citation statements)
references
References 25 publications
1
146
0
1
Order By: Relevance
“…To overcome these problems, synthetic biodegradable polymers have recently been tested as a delivery vehicle for osteoinductive agents. Earlier studies performed in our laboratory found that the PLA-PEG block copolymer with plastic properties works effectively as a BMP delivery system [33,34]. We then attempted to development a new biodegradable bone-inducing material by adding rhBMP-2 to porous b-TCP granules using a PLA-PEG polymer delivery system.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these problems, synthetic biodegradable polymers have recently been tested as a delivery vehicle for osteoinductive agents. Earlier studies performed in our laboratory found that the PLA-PEG block copolymer with plastic properties works effectively as a BMP delivery system [33,34]. We then attempted to development a new biodegradable bone-inducing material by adding rhBMP-2 to porous b-TCP granules using a PLA-PEG polymer delivery system.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of these scaffolds is shown by the fact that human tissue development is driven by surface adhesions and cellular contacts. [8][9][10][11][12] Therefore, we decided to perform this research with the aim to obtain a complete bone tissue formation. For this reason we studied the differentiation process leading to in vitro woven bone formation in order to better understand the mechanisms involved as well as bone tissue formation after transplantation in vivo.…”
mentioning
confidence: 99%
“…To optimize degradation of the polymer used to deliver rhBMP-2, para-dioxanone molecules were randomly inserted into the PLA segments of the PLA-PEG polymer without changing the total molecular weight [55].…”
Section: Synthetic Polymers For Bmp Delivery Systemmentioning
confidence: 99%